Communicable Diseases Intelligence volume 15 issue 14 - 15 July 1991 - whole issue - No author listed, (Communicable Diseases Intelligence, 1991)
Whole-issue pdf, comprising: Original articles Influenza update - No. 3/91 Arbovirus surveillance, New South Wales, 1989-91 Arbovirus surveillance, Victoria, 1990-91 Arbovirus surveillance, South Australia, 1990-1991 Listeriosis in Victoria, 1990 Australian HIV Surveillance Report, Volume 7, Number 5 (30 April 1991) CDI Notice to readers Polio Reference Laboratory established at Fairfield Hospital - request for isolates Communicable Diseases Surveillance CDI Laboratory Reporting Schemes Australian Sentinel Practice Research Network [ASPREN] National Notifiable Diseases Reports Viral Identifications from contributing laboratories - Period 19/06/1991 to 02/07/1991